Production of organic fertilizer from wet market food waste by composting method - Mohammad Roslan, Aisyatul Madihah (2020)
Most of the food waste on the wet market will be dumped in a way that causes proper deterioration of food waste without any recycling and waste systems also can induce pollution of the smell. The objective of this research is to produce organic fertilizer from food waste, to investigate the physiochemical organic fertilizer from food waste along with soil and mixture proportion using one-way ANOVA analysis. The treatments: To (soil as control), T1 (soil + compost) and T2 (organic compost from food waste). Food waste was collected and put into the moveable mesh wire as the compost bin with the consideration of all parameter that is related to aerobic composting. The result of this study showed from parameters of the physiochemical in To, T1 and T2 were in range of, 65-20 % for moisture content, 0.98-1.69 g/cm3 of bulk density, 7.13-7.55 of pH, 0.14-2.77 % of total nitrogen, 40.22-76.50 ppm of available phosphorus and 0.86-28.80 mg/L of available potassium, respectively. The statistical test of significant using ANOVA revealed that these were significantly different (P<0.05) between the values moisture content, bulk density, pH, total nitrogen, available of phosphorus and potassium in To, T1 and T2. It shows that the physiochemical value from organic composting is higher from the comparison with soil and mixture of soil and compost. To conclude, composting basic food waste on the wet market will provide a suitable organic fertilizer for use in plants and significantly reduce the amount of food waste produced to landfill.